2022
DOI: 10.3390/jcm11133704
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Developing Alzheimer’s Disease and Parkinson’s Disease in Patients with Inflammatory Bowel Disease: A Meta-Analysis

Abstract: Recently, a growing body of research has linked gut microbiota dysbiosis to central nervous system diseases, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), and has suggested that AD and PD pathology may take its origin from chronic inflammation in the gastrointestinal tract. Thus, this study aimed to elucidate whether inflammatory bowel disease (IBD) is associated with a higher risk of developing AD and PD as compared to the non-IBD population by conducting a meta-analysis. A thorough search of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Accumulating evidence suggests that gastrointestinal (GI) tract plays a role in Alzheimer's disease (AD): i) the GI symptoms are more prevalent in patients diagnosed with AD than in control populations [1]; ii) patients with inflammatory bowel disease (IBD) are at an increased risk of developing AD [2,3]; iii) there seems to be an overlap in genetic traits mediating susceptibility to AD and some GI disorders (e.g. gastroesophageal reflux disease, gastritis-duodenitis, peptic ulcer disease, diverticulosis) [4]; iv) intestinal microbiota of AD patients differs from that obtained from healthy controls [5][6][7]; v) animal studies support the existence of pathophysiological mechanisms by which gastrointestinal perturbations may lead to neurodegeneration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that gastrointestinal (GI) tract plays a role in Alzheimer's disease (AD): i) the GI symptoms are more prevalent in patients diagnosed with AD than in control populations [1]; ii) patients with inflammatory bowel disease (IBD) are at an increased risk of developing AD [2,3]; iii) there seems to be an overlap in genetic traits mediating susceptibility to AD and some GI disorders (e.g. gastroesophageal reflux disease, gastritis-duodenitis, peptic ulcer disease, diverticulosis) [4]; iv) intestinal microbiota of AD patients differs from that obtained from healthy controls [5][6][7]; v) animal studies support the existence of pathophysiological mechanisms by which gastrointestinal perturbations may lead to neurodegeneration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, metformin, an oral insulin sensitizer, increases the accumulation of Aβ therefore, its use may favor the development of AD (Picone et al, 2015). Also, a metaanalysis showed an increased risk of AD among patients with Crohn's disease and ulcerative colitis compared to the general population (Szandruk-Bender et al, 2022). In addition to this, growing evidence points to the influence of the digestive system and the disturbance of the gut microbiota to slow changes in the brain and beyond the development of AD.…”
Section: Ad Inflammatory Mechanisms and Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Since the pathology of dementia is heterogeneous, understanding the roles of IBD and related medications with specific diseases causing dementia, particularly AD, is more significant to future basic research and precision prevention strategy. After summarizing results from a limited number of studies, recent meta-analyses found a higher risk of AD for IBD patients compared with general healthy population, suggesting a potential pathological detrimental effect of IBD on the development of AD (Liu et al, 2022 ; Szandruk-Bender et al, 2022 ; Zhang et al, 2022 ; Zuin et al, 2022 ). Of note, these reviews did not cover several large-scale population-based studies, which reported extensively inconsistent results (Jussila et al, 2014 ; Sutton et al, 2019 ; Aggarwal et al, 2022 ; Ronnow Sand et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IBD therapies, such as immunosuppressants and TNF-α blockers, may play an important role in the AD development by controlling the inflammation severity (Sutton et al, 2019 ; Aggarwal et al, 2022 ; Ronnow Sand et al, 2022 ). However, the association between medications for managing IBD and risk of AD was not evaluated in previous meta-analyses (Fu et al, 2020 ; Liu et al, 2022 ; Szandruk-Bender et al, 2022 ; Zhang et al, 2022 ; Zuin et al, 2022 ). Thus, we performed an updated systematic review and meta-analysis by summarizing the published data to evaluate the associations of IBD and related medication exposure with risk of AD.…”
Section: Introductionmentioning
confidence: 99%